Experimental and numerical analysis of the tensile test on the A633 HSLA steel plate specimens with edge crack - Abi Shdid, Caesar (2014)
This paper presents an experimental and numerical study of the mechanical behavior of ASTM A633 highstrength low-alloy (HSLA) steel plate specimens with edge crack at the middle during the tensile test. Experimental analysis and numerical method are used to analyze the load-displacement curve for the steel specimens with various edge crack length. Four A633 HSLA steel plate specimens are tested in FIU’s Material Laboratory using a high capacity universal testing machine, and results are compared with the mesh-free and finite element results. A mesh-free method called Reproducing Kernel Particle Method (RKPM) is used to calculate the J-integral and load-displacement. RKPM is a mesh-free technology which is used to analyze the domain of interest only with particles using Ramberg-Osgood stress-strain relationship. A numerical analysis was performed using the finite element program ANSYS to exhibit the efficacy of RKPM in analyzing crack problems. This paper studies the effect of crack length on the load-displacement curve and the J-integral of A633 HSLA specimens after tensile tests. Results of load-displacement curves and J-integral curves found using the experimental, finite element, and mesh-free methods were compared and validated against each other for samples with various crack lengths.